Mixed Hill Cipher methods with triple pass protocol methods - Liqaa Saadi Mezher; Ayam Mohsen Abbass (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Hill Cipher is a reimbursement coding system that converts specific textual content codes into numbers and does no longer exchange the location of fixed symbols. The symbol modifications simplest in step with the English letter table inclusive of (26) characters handiest. An encoded Hill Cipher algorithm was used that multiplication the square matrix of the apparent text with a non-public key and then combined it with the Triple Pass Protocol method used to repeat the encryption three times without relying on a personal key. Also, you could decode the code and go back it to the express textual content. The cause of mixing algorithms is to cozy the message without any key change among the sender and the recipient.